PENERAPAN METODE TILAWATY UNTUK MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN SISWA KELAS VIII DI MTS NURUL IKHLAS KARI - Mauliza Mauliza; Sopiatun Nahwiyah; Ikrima Mailani (JOM FTK UNIKS (Jurnal Online Mahasiswa FTK UNIKS), 2022)
The problem in this study originated from the low ability to read the Qur'an of class VIII students at MTs Nurul Ikhlas Kari, which was caused by the ineffectiveness of the method used, namely the Memorization Method. This is the background for researchers to conduct research by applying the Tilawaty Method, to improve the ability to read the Qur'an of class VIII students. The Tilawaty method is Al-Qur'an learning that combines classical and individual reading and listening so that it helps students to improve and launch their reading of the Qur'an. The purpose of this study was to see and find out how much improvement in the ability to read the Qur'an of class VIII students with the application of the Tilawaty Method at MTs Nurul Ikhlas Kari. The method used in this study is a quantitative method. The type of research is experimental research in the form of One-Group Pretest-Posttest Design. The subjects in this study were students of MTs class VIII, totaling 33 students. Consisting of 13 male students and 20 female students. The data collection techniques are observation, interviews, tests, and documentation. The results showed that learning the Qur'an using the Tilawaty Method could improve students' reading skills of the Qur'an. This is evidenced by the increase between the pretest and posttest scores. The average value of the pretest is 71,515 while the average value of the post test is 77,470. Then from the results of the Wilcoxon Signed Rank Test, it can be seen that Ha is accepted and H0 is rejected, the reason being Asyimp. Sig (2-tailed) of 0.000 which means <0.05. So it can be concluded that there is an increase in the ability to read the Qur'an of class VIII students with the application of the Tilawaty Method at MTs Nurul Ikhlas Kari.